2024
DOI: 10.1590/1519-6984.251410
|View full text |Cite
|
Sign up to set email alerts
|

Dietary habits of lesser bandicoot rat (Bandicota Bengalensis) in an agro-ecosystem, Pothwar Plateau, Pakistan

Abstract: Dietary habits of bandicoot rats (bandicota bengalensis) were investigated in the agricultural crops of the Pothwar Plateau, Pakistan by analysing stomach contents. The research activities were conducted in major field crops including wheat-groundnut and in the fallow lands during non-crop season at the field boundaries. The specimens were captured from the fields using kill/snap traps, and dissected to collect their stomach samples for laboratory analysis. Light microscopic slides of the plant material were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Results of the present study support; yet a non-significant difference in the damage pattern at the flowering and maturity stages indicate that either population of the rodent species is greater in the area or other vegetation is not preferred and / or limited. Rodent preferences (especially the Bendicota bengalensis) for the groundnut during the summer season has also been documented (Baig et al, 2021). Similarly, Indian crested porcupine (Hystrix indica) is also widely distributed rodent species in the study area and has been reported by the farmers as a serious pest of the groundnut crop.…”
Section: Resultsmentioning
confidence: 65%
“…Results of the present study support; yet a non-significant difference in the damage pattern at the flowering and maturity stages indicate that either population of the rodent species is greater in the area or other vegetation is not preferred and / or limited. Rodent preferences (especially the Bendicota bengalensis) for the groundnut during the summer season has also been documented (Baig et al, 2021). Similarly, Indian crested porcupine (Hystrix indica) is also widely distributed rodent species in the study area and has been reported by the farmers as a serious pest of the groundnut crop.…”
Section: Resultsmentioning
confidence: 65%
“…Among several rodent species, Bandicota bengalensis (Gray, 1835) has been reported throughout Southeast Asia (Singla & Parshad 2010;Singleton et al 2021). Besides causing serious damage to food crops (Singla & Babbar 2012;Munawar et al 2019;Baig et al 2021), it is also involved in spread of several diseases and is a host of parasites (Singla et al 2008(Singla et al , 2016Meerburg et al 2009;Brar et al 2021). Various methods are applied worldwide to reduce losses caused by rodent pests, but the use of rodenticides as a lethal method is considered the most practical, economical, and effective (Buckle & Eason 2015;Witmer 2019).…”
Section: Introductionmentioning
confidence: 99%
“…2019; Baig et al. 2021), it is also involved in spread of several diseases and is a host of parasites (Singla et al. 2008, 2016; Meerburg et al.…”
Section: Introductionmentioning
confidence: 99%